Karakteristik Ekstrak Metanol Daun Mangrove (Rhizophora mucronata) pada Perlakuan Ukuran Partikel dan Waktu Maserasi - Diana, Eka Nur; Wrasiati, Luh Putu; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2021)
Mangrove leaf (Rhizophora mucronata) is one part of the plants that has not been used optimally. This study aims to determine the effect of particle size and maceration time on the characteristics of the mangrove leaf methanol extract (Rhizophora mucronata) and to determine the particle size and maceration time so as to produce the best characteristics of the mangrove leaf methanol extract (Rhizopora mucronata). This study used a factorial Randomized Block Design (RBD) with two factors. The first factor is the particle size which consists of 40, 60 and 80 mesh. The second factor is the maceration time which consists of 24, 36 and 48 hours. The data were analyzed by analysis of variation and if the treatment had an effect, it was continued with the Tukey test. The results showed that the treatment of particle size and maceration time had a very significant effect on the yield, total flavonoids, IC 50 and color intensity (L*, a*, b*), while the interaction between particle size and maceration time had a significant effect on total flavonoids, and IC 50 . The particle size of 60 mesh with a maceration time of 36 hours can increase the average value of total flavonoids, IC 50 , level of redness (a*) and level of yellowness (b*). Particle size 60 mesh and maceration time 36 hours is the best treatment to obtain methanol extract of mangrove leaves with the following characteristics: yield 33.90 ± 1.502%, total flavonoids 82.03 ± 1.24 mg QE/g, antioxidant activity IC 50 71.06 ± 1.84 ppm , the level of brightness (L*) 23.93 ± 0.559, the level of redness (a*) 11.12 ± 0.568, and the level of yellowness (b*) 10.15 ± 0.510. Keywords:   Mangrove leaves (Rhizhopora mucronata), extraction, particle size, maceration time